(untitled) (Economia Aplicada, 1999)
The development of credibility and temporal inconsistency literature has contributed to non inflationary policy formulation in many countries. When a policy is implemented, the governmental credibility is pointed out as the main problem faced by policymakers. In this paper, credibility of economic policy is estimated analyzing the relationship between real interest rate differential and unemployment. The results suggest that the economic policy was not credible in sub-periods 1 and 4 (February 1991 to December 1992 and July 1996 to July 1998) and credible in sub-period 3 (June 1994 to June 1996). In sub-period 2 it was not possible to detect if the economic policy implemented was credible or not.